Kierowanie przez nauczyciela polonistę własnym rozwojem zawodowym w aspekcie funkcji określonych rodzajów wiedzy i umiejętności = About the development leading by the "polish language" teatcher in aspects of many sorts of knowledge and skills - Pękala, Bolesław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article is based on opinions many authors and presents the usefulness (functions) of many different sorts of knowledge. Each more important branch of knowledge and many different aspects of scienses are presented in co-relations between the teatchers personality and the subject named "Polish language". This article points to the necessity and particularly importence for his personality development.
Keywords: nauczyciele; rozwój zawodowy